PEMANFAATAN BAHAN TEKNIS KNO3, CaCl2, MgSO4, KH2PO4 SEBAGAI HARA MAKRO DAN Benzil Adenin DALAM PERBANYAKAN JATI (Tectona grandis L) SECARA IN VITRO - karyanti, karyanti; royani, juwartina ida (Badan Pengkajian dan Penerapan Teknologi, 2012)
Indonesia is a major producer of teak after India and will gradually decrease if not followed by replanting. In general, teak plants propagated through seeds but have many disadvantages. Teak plant propagation using in vitro technique being an alternative to get the mass production of teak clones. In vitro technique, to some extent, needs a high cost particularly in using pure chemical substance. As an alternative solution, pure chemical substance can be substituted by using a few technique chemical substances such as KNO3, CaCl2, MgSO4, and KH2PO4. The aim of this research was to evaluated induction of shoot teaks, planted on different media with macro element substituted by different chemicals such as KNO3, CaCl2, MgSO4, and KH2PO4. The result showed that using the same concentration between 2 different chemical substances on teak shoot induction, there was no different shoot growing in teak propagated between 2 media.